2016
DOI: 10.1111/apt.13657
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐related mortality in countries of the developed world: an ecological study approach to explain the variability

Abstract: Hepatitis B infection, alcohol consumption and GDP, but not hepatitis C or other factors, explain most of the variance of liver-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…2 Von Wulffen and colleagues present a 'big picture' of the burden in Western countries by correlating population statistics on liver deaths with prevalence of common risk factors of chronic liver disease, including hepatitis B and C, alcohol intake per capita, metabolic syndrome and other comorbidities and environmental factors. 3 Overall, liver deaths were associated with alcohol intake and hepatitis B but not with hepatitis C, human immunodeficiency virus (HIV), and the metabolic syndrome. Although some information on the competing risk of dying before liver disease progression is missing, the study underlines how liver disease progression models, including hepatitis C, may be complex and interlaced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Von Wulffen and colleagues present a 'big picture' of the burden in Western countries by correlating population statistics on liver deaths with prevalence of common risk factors of chronic liver disease, including hepatitis B and C, alcohol intake per capita, metabolic syndrome and other comorbidities and environmental factors. 3 Overall, liver deaths were associated with alcohol intake and hepatitis B but not with hepatitis C, human immunodeficiency virus (HIV), and the metabolic syndrome. Although some information on the competing risk of dying before liver disease progression is missing, the study underlines how liver disease progression models, including hepatitis C, may be complex and interlaced.…”
mentioning
confidence: 99%
“…Indeed, several cohort studies in hepatitis C infected individuals demonstrated that in the absence of risk factors (such as alcohol consumption), progression to severe liver disease may take decades or may not occur at all in the vast majority of patients. 3,4 One problem for a substantial group of patients with chronic hepatitis C is impaired quality of life (QoL). 5 Patients with advanced fibrosis have impairment in quality of life.…”
mentioning
confidence: 99%
“…2 Several nutraceuticals have been investigated in NASH; well known among these is the association between coffee consumption and fibrosis reduction in NASH. 3 Poly-unsaturated fatty acids, and polyphenols such as silymarin, curcumin and resveratrol have been studied in pre-clinical models and small-scale trials demonstrating reduction in markers of liver injury, inflammation, apoptosis and oxidation.…”
Section: Acknowledgementmentioning
confidence: 99%
“…8 Therefore, inhibition of ROS signalling presents an attractive therapeutic opportunity. 2 In this single blind, cross-over trial, 19 NASH subjects and 19 age, gender and body mass index matched controls were randomised to 20 g dark chocolate or milk chocolate twice a day for 2 weeks, with a 1 week washout period in between. By self-monitoring, caloric intake was identical among subjects, and adjusted for chocolate-derived energy.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation